CO2-laser for the genitourinary syndrome of menopause. How many laser sessions?. (October 2017) - Athanasiou, Stavros; Pitsouni, Eleni; Falagas, Matthew E.; Salvatore, Stefano; Grigoriadis, Themos
Highlights: An extra fourth or fifth session may increase the efficacy of CO2 -laser therapy for genitourinary syndrome of menopause. The dyspareunia-free rate may increase from 27% to 81% following three to five sessions. The dryness-free rate may increase from 36% to 86%, depending on the number of laser sessions. Up to 84% of participants may resume normal sexual function after laser therapy. Up to 100% of participants may regain premenopausal ratings on indexes of vaginal atrophy. Abstract: Objectives: The aim of this prospective study was to assess the efficacy of 3, 4 or 5 CO2 -laser sessions for the management of the genitourinary syndrome of menopause (GSM). Methods: Postmenopausal women with moderate to severe symptoms of dyspareunia, wanting to resume/retain sexual activity, were treated with 3–5 laser sessions depending on symptom severity/presence, sexual function, clinical findings and women's preference following the third laser application. Main outcomes: Severity of dyspareunia, dryness, sexual function, sexual satisfaction and frequency of sexual intercourse defined the primary outcomes. Vaginal Maturation Value (VMV) and Vaginal Health Index Score (VHIS) defined the secondary ones. Results: Fifty-five women received three sessions, 53 an extra fourth and 22 an extra fifth. Following the third, fourth and fifth laser sessions, respectively: dyspareunia completely regressed in 15/55 (27%), 32/55 (58%) and 38/47 (81%) of participants; dryness completely regressed in 20/55 (36%), 36/55 (66%) and 44/51 (86%); normal sexual function resumed in 23/55 (41%), 37/54 (69%) and 41/49 (84%); VMV regained non-atrophic values in 29/55 (53%), 38/55 (69%) and 42/50 (84%); and VHIS regained non-atrophic values in 44/55 (80%), 53/55 (96%) and 55/55 (100%) of participants. Conclusion: Results of this study indicate that CO2 -laser therapy may contribute to complete regression of dyspareunia and dryness and reestablishment of normal sexual function in postmenopausal women, in a dose-response manner. An extra fourth or fifth session may further increase the GSM symptom-free rate.